New age spirituality: rethinking religion - Gilhus, Ingvild Sælid; Sutcliffe, Steven J. (Acumen, 2013)
New Age and holistic beliefs and practices - sometimes called the ""new spirituality"" - are widely distributed across modern global society. The fluid and popular nature of new age makes these movements a very challenging field to understand using traditional models of religious analysis. Rather than treating new age as an exotic specimen on the margins of ''proper'' religion, ""New Age Spirituality"" examines these movements as a form of everyday or lived religion. The book brings together an international range of scholars to explore the key issues: insight, healing, divination, meditatio